Sirri Marriage Talaq and Legal Consequences on Children's Rights from an Islamic Legal Perspective - Zahra Lailatul Wahida; Ani Mardiantari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This study discusses the practice of talaq in nikah sirri and its legal consequences on children's rights from the perspective of Islamic law in Bumi Raharjo Village, Bumiratu Nuban District, Central Lampung Regency. The problem studied is how the practice of talaq is carried out in sirri marriage and how its implications are for the fulfillment of children's rights, especially alimony, hadhanah, and certainty of legal status. This study aims to analyze the factors that cause the occurrence of talaq nikah sirri and assess the legal consequences of children's rights based on the perspective of fiqh and contemporary Islamic law. The method used is field research with a sociological and qualitative approach. Primary data was obtained through in-depth interviews with three respondents of sirri marriage perpetrators, religious leaders, and village officials, while secondary data was obtained from fiqh literature, Compilation of Islamic Law, and related laws and regulations. The results of the study show that talaq in nikah sirri is carried out orally without going through the Religious Court and without official registration, so it does not have administrative legal force. As a result, the fulfillment of children's rights, especially alimony, does not run optimally and is often neglected. Normatively, Islamic law still requires fathers to provide support, but in social practice the absence of formal legality causes weak legal protection for children.